Nan gua cun de long - Bing, Bo, 1957- (Beijing, China : Volume Press, 2022)
Wang Yimei Bingbo classic fairy tale Zhuyin full color beauty painting The great writer who walked into the textbook wrote a little fairy tale for you
Parallel text in Chinese and Hanyu Pinyin.
Keywords: Tales, Chinese; Children's stories, Chinese